Tolman & White, Book and Job Printers; Atwood's Pure Alcohol, A.H. Roby & Co., Furniture; Robert Webb, dealer in Black Leads - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of Tolman & White, Book and Job Printers; Atwood's Pure Alcohol, A.H. Roby & Co., Furniture; Robert Webb, dealer in Black Leads from the 1870 Boston City Directory